Comparative Evaluation of Microleakage of Bioactive, Ormocer, and Conventional GIC Restorative Materials in Primary Molars: An In Vitro Study Microleakage of Three Restorative Materials. (11th March 2022) - Jain, Khushboo; Katge, Farhin; Poojari, Manohar; Shetty, Shilpa; Patil, Devendra; Ghadge, Sanjana
Abstract : This in vitro study aimed to evaluate and compare the microleakage of bioactive, ormocer, and conventional glass ionomer cement (GIC) restorative materials in primary molars. In this study, class V cavities were prepared on the buccal surface of 75 noncarious extracted primary molars. The teeth were then restored as per the groups assigned. Group A, group B, and group C used bioactive restorative materials, ormocer restorative materials, and conventional GIC restorative materials for restorations, respectively. The teeth were then thermocycled and subjected to microleakage analysis via dye penetration. The microleakage scores were compared for differences using the Kruskal–Wallis test. This was followed by multiple pairwise comparisons using the Dunn test. All testing was carried out using a 'p' value of <0.05. The percentage of samples showing microleakage score 0 depicting no dye penetration was highest for group A (56%) followed by group C (44%) and group B (12%). Statistical analysis revealed highest microleakage with group B, which was statistically significant (p  < 0.05). Microleakage was evident in all the materials tested. The lowest microleakage was seen with bioactive restorative material.